Gastric heterotopia in the ileum mimicking Meckel's diverticulum - Reza Shojaeian; Negar Nekooei; Paria Dehghanian (Elsevier, 2022)
Gastric heterotopia is the presence of normal gastric tissue elsewhere than the stomach. It has been reported in the alimentary tract from oropharynx to rectum. It is common in esophagus, duodenum, and in congenital anomalies such as Meckel's diverticulum (MD) and duplications, however it is rarely found in the small intestine beyond the ligament of Treitz without the accompanying anomalies. In this presentation, we report a 3-year-old female with chronic anemia and abnormal uptake in technetium99 pertechnetate scintigraphy in right lower quadrant of abdomen which lead to diagnosis of ectopic gastric tissue in ileum, outside of the MD.